Behcets Disease Presenting as Fever of Unknown Origin : A Case Report (BIRDEM Medical Journal, 2013)
Behcets disease (BD) is an inflammatory disease characterized by recurrent oral aphthous ulcers and numerous systemic manifestations. The underlying cause of Behcets disease is unknown. As with other autoimmune diseases, the disorder may represent aberrant immune activity triggered by exposure to an antigen, perhaps infectious, in patient with a genetic predisposition to develop the disease. Here we are reporting a case of Behcets disease in a 50 year old gentleman who presented with fever, recurrent oral ulcers and genital ulcer. Diagnostic workup excluded other possible diseases. Pathergy test was positive. Prednisolone was started along with other supportive therapy and patient subsequently improved. Birdem Med J 2013; 3(1): 50-53 DOI: http://dx.doi.org/10.3329/birdem.v3i1.17128